Contribution of non-timber forest products to the livelihood of farmers in coffee growing areas: evidence from Yayu Coffee Forest Biosphere Reserve. Issue 9 (28th July 2020) - Beyene, Abebe D.; Mekonnen, Alemu; Hirons, Mark; Robinson, Elizabeth J. Z.; Gonfa, Techane; Gole, Tadesse W.; Demissie, Sheleme
Abstract : This article examines the role of forest products in the livelihoods of forest-dependent households in the Yayu Coffee Forest Biosphere Reserve in the South Western part of Ethiopia. Unlike many forest landscapes, households in Yayu district cultivate their primary crop, coffee, in a complex landscape. Sampled households ( n  = 241) were chosen based on the stratified random sampling method. We employ both descriptive statistics and econometric regression to assess the extent of forest product use and analyse the determinants of forest income, respectively. We find that relatively poor households are more dependent on forest resources as a share of total income than better-off households. We further find that households in the Yayu district use non-timber forest products (NTFPs) mainly for consumption. The current zoning arrangements around the biosphere reserve support the provision of NTFPs, particularly for poorer households and should be considered for replication in other complex landscapes.